APPLICATION OF THE LAW OF QUALIFICATION OF CRIMINAL MAKING AGAINST NARCOTIC USERS IN THE LEVEL INVESTIGATIONS IN WEST ACEH POLRES - Mahdian Siregar; Marlina Marlina; Adil Akhyar (LPPM YPITI, 2021)
As a measure of action that can be imposed on an addict is Article 127 jo Article 54 jo Article 103 of the Narcotics Act. However, the substance of the Narcotics Act does not provide a clear conception of narcotics abusers that are categorized as users, addicts and victims of narcotics, so that they can be clearly and decisively distinguished from narcotics dealers and precepors. As a result, the application of the law against drug users, has not yet fully realized legal certainty. The problems in this study are about how the qualifications of narcotics abusers and the application of criminal law against narcotics abusers and obstacles to police investigators in the Southwest Aceh Narcotics Police Unit in applying the qualifications of narcotics abusers in?This type of research is empirical juridical research. The data analysis used in this study is qualitative data analysis. Based on the results of the study, the qualifications of narcotics abusers are divided into three types, namely: users, addicts and victims of narcotics abusers. However, the subjects of these qualifications are not clearly regulated in the Narcotics Act. The application of criminal law against narcotics abuse by investigators of the Southwest Aceh Narcotics Unit has not yet been able to be applied to the maximum, therefore certain conditions are difficult to declare a person as an addict and victim of narcotics abuse. The obstacles of investigators in applying the qualifications of narcotics abusers are influenced by the legal subsystem in the narcotics criminal legal system. Substantially the Narcotics Law does not clearly regulate narcotics crime based on its subjects. Viewed from the aspect of the legal structure, narcotics law enforcement has not yet led to law enforcement efforts, particularly the National Police to prevent, protect and save the Indonesian people from abuse of Narcotics.